2013
DOI: 10.1371/journal.pgen.1003196
|View full text |Cite|
|
Sign up to set email alerts
|

NBR1-Mediated Selective Autophagy Targets Insoluble Ubiquitinated Protein Aggregates in Plant Stress Responses

Abstract: Plant autophagy plays an important role in delaying senescence, nutrient recycling, and stress responses. Functional analysis of plant autophagy has almost exclusively focused on the proteins required for the core process of autophagosome assembly, but little is known about the proteins involved in other important processes of autophagy, including autophagy cargo recognition and sequestration. In this study, we report functional genetic analysis of Arabidopsis NBR1, a homolog of mammalian autophagy cargo adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
433
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(465 citation statements)
references
References 56 publications
27
433
2
3
Order By: Relevance
“…(24). Recent reports suggested that plant NBR1 binds to polyubiquitinated substrates similar to the binding in mammalian counterparts, although the identity of individual plant proteins targeted by NBR1 for autophagic destruction has yet to be determined (22,24). We found direct ubiquitin-independent interaction of NBR1 with CaMV P4.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…(24). Recent reports suggested that plant NBR1 binds to polyubiquitinated substrates similar to the binding in mammalian counterparts, although the identity of individual plant proteins targeted by NBR1 for autophagic destruction has yet to be determined (22,24). We found direct ubiquitin-independent interaction of NBR1 with CaMV P4.…”
Section: Discussionsupporting
confidence: 53%
“…We next monitored the expression of the autophagy core genes ATG8a and ATG8e and the autophagy receptor NBR1, which are all elevated as part of an induced autophagy response during plant heat stress (22). Both CaMV isolates stimulated the accumulation of the autophagic markers' transcripts and proteins relative to the noninfected control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Consistent with the role of ATG8 during abiotic stress (Xiong et al, 2007) as well as its transcriptional induction under heat stress (Zhou et al, 2013), paraquat treatment in BdbZIP10o/e plants significantly increased BdATG8 levels above that of wild-type treated plants (Fig. 5).…”
Section: Bdbzip10 Overexpression Enhances Transcription Of Protectivesupporting
confidence: 74%
“…NBR1 functions as a pexophagy receptor in mammals (Deosaran et al, 2013). It will be interesting to learn whether Arabidopsis NBR1 (Svenning et al, 2011;ZientaraRytter et al, 2011), which functions in autophagy of insoluble ubiquitinated aggregates (Zhou et al, 2013), similarly targets peroxisomes for pexophagy in Arabidopsis and whether any ubiquitinated proteins in the peroxisome membrane are required for pexophagy. It is noteworthy that several peroxisomal proteins are found in a recent proteomic analysis of ubiquitinated Arabidopsis proteins (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%